PENDIDIKAN ANAK BERKEBUTUHAN KHUSUS (TUNA DAKSA) DI SEKOLAH LUAR BIASA (SLB) DESA TENTE KEC. WOHA - Zumratun, Zumratun (FASHLUNA, 2023)
This paper discusses how to educate and guide children who have special limitations and have disabilities in their limbs, one of which is a disabled child. Children who have physical or mental limitations have the right to study and the government has provided special schools for these children. Seeing the reality that is happening now, there are many children who do not want to pursue education due to physical disabilities and most children do not even want to leave the house because of this. The need for the role of parents and teachers who can guide children who have special limitations, especially children with physical disabilities are children who have movement disorders in the limbs caused by neoro-muscular and bone structure abnormalities that are congenital or due to accidents. Guidance and services that are appropriate to the child's condition must be applied and carried out by parents and teachers. Teachers provide services and education when at school while parents guide when children are at home so that development is good in terms of emotional, educational and others. can be controlled by parents and teachers and children can study like normal children in general.